(untitled) (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Breast cancers in less than 40 years of age group usually present with aggressive biology and has poor prognosis. The aim of this study was to see clinic-pathological and hormone receptors of breast cancers in young women and compare with less than 40 year age group. Methods: Prospective analysis of 97 breast cancer in patients less than 40 years out of total 373 patients (26%) over a period of 8 years (2007 Jan to 2014 Dec) was carried out at the Department of Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Result: Among the young women diagnosed with breast cancer, the mean age was 34.5±6.2 years. Mean tumour size was larger in younger women (5±2.5 vs 4.5±2.4 cm). Locally advanced disease was higher in younger patients (55% vs 47%). Lymphatic and vascular invasions were higher (63% vs 35% and 40% vs 25%). Grade II and III tumours was higher (56% vs 25%). ER, PR and HER2 positivity was detected in 46.9%, 48.9% and 28.9% respectively. Significant lower ER or PR expression (34.5% vs 54%) was seen in younger women, p=.002.Triple negative tumours (ER -ve, PR -ve and HER2 -ve) was proportionately higher in younger patients (23% vs 13.7%, p=.043). Conclusion: Young Nepali women presents one quarter of all female breast cancers, more frequently locally advanced with aggressive tumour biology like ER/PR negative and triple negative breast cancers. Journal of Society of Surgeons of Nepal, 2015; 18 (2), page: 16-19